Structural determinants conferring unusual long life in human serum to rattlesnake‐derived antimicrobial peptide Ctn[15‐34]. (17th July 2019) - Pérez‐Peinado, Clara; Dias, Susana A.; Mendonça, Diogo A.; Castanho, Miguel A.R.B.; Veiga, Ana S.; Andreu, David
Abstract : Ctn[15‐34], a downsized version of the snake venom cathelicidin‐like peptide crotalicidin (Ctn), shows an unusually high lifespan ( t 1/2, approximately 12 h) in human serum, which significantly adds to its promise as an antimicrobial and antitumor agent. Herein we investigate the role of Ctn[15‐34] structure on serum survival. Using a set of analogs, we show that C‐terminal amidation, as well as the specific layout of the Ctn[15‐34] sequence—a helical N‐terminal domain followed by a hydrophobic domain—is crucial for slow degradation, and any change in their arrangement results in significantly lower t 1/2 . Aside from the privileged primary structure, features such as self‐aggregation can be ruled out as causes for the long serum life. Instead, studies in other protease‐rich fluids suggest a key role for certain human serum components. Finally, we demonstrate that Ctn[15‐34] is able to induce bacterial death even after 12‐hour pre‐incubation in serum, in agreement with the proteolytic data. Altogether, the results shed light on the uncommon stability of Ctn[15‐34] in human serum and confirm its potential as an anti‐infective lead. Abstract : The unusual long half‐life in serum of Ctn[15‐34], a promising antimicrobial peptide from rattlesnake venom, is investigated. Structurally, Ctn[15‐34] seems to possess a privileged framework, since any change on its structure results in lower stability. Binding to serum components seems somehow to be involved in its extended half‐life in serum yet without hampering biological activity, as the peptide preserves antimicrobial activity even after 12‐hour pre‐incubation in serum.